GAMBARAN PENYESUAIAN DIRI MAHASISWA BARU - Iflah Iflah; Winda Dwi Listyasari (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2013)
This research aims to describe the self adjustment of 2012 new students of Psychology programs, as well as determine the factors affecting self adjustment on 2012 new students of Psychology Programs. This research conducted at the D campus of the Psychology Program, Universitas Negeri Jakarta. This research used sequential mixed methods which conducted in two phases, starting with quantitative phase and followed by qualitative phase. Based on the result of quantitative phase, three respondents were selected to join in qualitative phase. Qualitative data collected by using interview technique. The results showed that 49 respondents (96,07%) include in the high category of self adjustment and 2 respondents (3,9%) include in the low category. The factors affecting self adjustment of new students of Psychology Programs are: 1) peer environment, 2) the learning process, 3) willingness to learn, 4. activities or programs outside the academic activities.